Permanent His‐bundle pacing using distal His‐bundle electrogram‐guided approach in patients with atrioventricular block. Issue 11 (20th September 2021) - Suga, Kazumasa; Kato, Hiroyuki; Inden, Yasuya; Yanagisawa, Satoshi; Murakami, Hisashi; Kada, Kenji; Tsuboi, Naoya; Murohara, Toyoaki
Abstract: Background: Permanent His‐bundle pacing (HBP) is effective and safe; however, the success rate of HBP is low, especially in patients with infranodal block. This study aimed to assess the efficacy and feasibility of HBP implantation using an electrophysiological guided approach targeting a distal His‐bundle electrogram (HBE) in patients with atrioventricular block (AVB). Methods: Thirty‐four consecutive patients with AVB (infranodal block in 28 patients) who underwent HBP were enrolled. During implantation, we attempted to target the distal part of the HBE (distal HBE) beyond the block site based on unipolar mapping. The His‐capture threshold was evaluated for 1 year after implantation. Results: HBP was achieved in 26 patients and in 21 patients (75%) with infranodal block. Detection of distal HBE was significantly higher in the successful HBP group than in the HBP failure group (65.4% vs. 0%, p  = .001). Among 15 patients with intra‐Hisian block, 14 patients (93%) successfully achieved HBP with distal HBE detection. During the 1‐year follow‐up period, an increase in His‐capture threshold by ≥1.0 V at 1.0 ms occurred in five (19.2%) of 26 patients. The increased His‐capture threshold group exhibited significantly less detection of distal HBE (20% vs. 76.2%; odds ratio 0.078, 95% confidence interval 0.07–0.87, p  = .038) and a higher His‐capture threshold at implantation (2.0 ± 1.1 V vs. 1.1 ± 0.9 V; odds ratio 1.702, 95% confidence interval 1.025–2.825, p  = 0.04) than the non‐increased His‐capture threshold group. Conclusion: HBP implantation guided by distal HBE approach may be feasible with subsequent stable pacing in patients with intra‐Hisian and atrioventricular nodal block.